2012
DOI: 10.1029/2012wr012525
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of acoustic emissions induced by fluid front displacement in porous media

Abstract: The dynamics of fluid displacement in porous media often affect phase entrapment and shape macroscopic transport properties and thus are of considerable interest for a range of natural and engineering applications. The macroscopic motion of a displacement front is composed of numerous abrupt pore‐scale invasion events that involve rapid interfacial jumps and reconfigurations with associated mechanical and interfacial energy release detectable as acoustic emissions (AE). We conducted systematic experiments of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 57 publications
6
31
1
Order By: Relevance
“…volume quantities. In this section we show that the proposed diffuse-interface model is able to capture pressure fluctuations generated as liquid-vapor interfaces advance, in accordance with experimental observations [77][78][79][80][81][82] (Figs. 20-23).…”
Section: Pressure Fluctuations and Pressure Pulses Due To Advancsupporting
confidence: 62%
See 2 more Smart Citations
“…volume quantities. In this section we show that the proposed diffuse-interface model is able to capture pressure fluctuations generated as liquid-vapor interfaces advance, in accordance with experimental observations [77][78][79][80][81][82] (Figs. 20-23).…”
Section: Pressure Fluctuations and Pressure Pulses Due To Advancsupporting
confidence: 62%
“…In particular, we show that the diffuse-interface model is able to capture pressure fluctuations 084302-2 generated as liquid-vapor interfaces advance, in accordance with experimental observations [77][78][79][80][81][82]. We also conclude that phase-change fronts are controlled by heterogeneity, a feature that is typical of evaporation fronts, interpreted as modified invasion percolation processes [83][84][85][86][87].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The capillary-weighted redistribution employed in T- O [2008] moved water vertically in the profile and was incorrect because our intention in simulating this process is that it is a free-energy minimization process that involves changes in interfacial energy, not potential energy. In the improved method, we call this process capillary relaxation after Moebius et al [2012], as it moves water from regions of low capillarity to high capillarity at the pore scale and at the same elevation, producing no advection at or beyond the REV scale.…”
Section: Finite Water-content Discretizationmentioning
confidence: 99%
“…In unsaturated soils in the presence of gravity, water infiltrating into a partially saturated porous medium flows faster through larger pores because they are the most efficient conductors [Gilding 1990]. Capillarity then acts to move this advected water from these larger pore spaces into smaller pore spaces at the same elevation in a process we call ''capillary relaxation'' after Moebius et al [2012] who have observed this phenomenon using acoustic emissions.…”
mentioning
confidence: 99%